PENGARUH IKLIM ORGANISASI, KOMPETENSI DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PADA PT. BALI SANTOSA WISATA MY SWING BALI - Ni Wayan Ika Ardhyanti; Anak Agung Dwi Widyani; I Dewa Made Arik Permana Putra (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2024)
Human resources are a very important element in the movement and progress of a organization. Employees who have the ability to carry out their duties and responsibilities well can help the organization to continue to develop. This research aims to determine the influence of organizational climate, competence and communication on employee performance at PT. Bali Santosa My Swing Bali Tourism. The population of this research is all employees at PT. Bali Santosa My Swing Bali Tourism consisted of 60 people, using the census method so that the entire population was sampled. The data sources in this research are primary data and secondary data. Data collection techniques used in this research include observation, interviews, documentation and questionnaires. The analytical tool used to test the hypothesis is multiple linear regression analysis using the SPSS version 26 program. Based on the analysis results, it shows that organizational climate has a positive and significant effect on employee performance. Competency has a positive and significant effect on employee performance. And communication has a positive and significant effect on employee performance.